Injuries sustained by earthquake relief workers: a retrospective analysis of 207 relief workers during Nepal earthquake. Issue 1 (December 2016) - Du, Feizhou; Wu, Jialing; Fan, Jin; Jiang, Rui; Gu, Ming; He, Xiaowu; Wang, Zhiming; He, Ci
Abstract Background This study aimed to analyse the injuries sustained by rescue workers in earthquake relief efforts in high altitude areas for improving the ways of how to effectively prevent the injuries. Methods The clinical data of 207 relief workers from four military hospitals in Tibet, who were injured in the Tibetan disaster areas of China during '4.25' Nepal earthquake rescue period, was retrospectively analyzed. The demographic features, sites of injury and causes of injury were investigated. Results The most frequently injured sites were the ankle-foot and hand-wrist (n  = 61, 26.5 %), followed by injuries in leg-knee-calf (n  = 22, 9.6 %), head-neck (4.87 %), thoracic and abdominal region (2.6 %) and lower back (3.9 %). The specific high-altitude environment increased the challenges associated with earthquake relief. Discussion The specific plateau environment and climate increased the burden and challenge in earthquake relief. The injury distribution data shown in this study demonstrated that effective organization and personnel protection can reduce the injury occurrences. Conclusion Relief workers were prone to suffering various injuries and diseases under specific high-altitude environment.